2011
DOI: 10.1371/journal.pone.0020696
|View full text |Cite
|
Sign up to set email alerts
|

Hdac6 Knock-Out Increases Tubulin Acetylation but Does Not Modify Disease Progression in the R6/2 Mouse Model of Huntington's Disease

Abstract: Huntington's disease (HD) is a progressive neurodegenerative disorder for which there is no effective disease modifying treatment. Following-on from studies in HD animal models, histone deacetylase (HDAC) inhibition has emerged as an attractive therapeutic option. In parallel, several reports have demonstrated a role for histone deacetylase 6 (HDAC6) in the modulation of the toxicity caused by the accumulation of misfolded proteins, including that of expanded polyglutamine in an N-terminal huntingtin fragment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
66
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 61 publications
4
66
0
Order By: Relevance
“…Our findings agree, however, with other studies in neurons, where HDAC6 inhibition alleviated abnormal A and tau accumulation [53,64], and with in vivo HDAC6-knockout in R6/2 mice showing no increase in mHtt aggregates [65]. Thus, as previously suggested [65], some of the effects of HDAC6 in cell-lines may not apply to neurons.…”
Section: Striatal and Cortical Neurons Differ In Mhtt Proteostasis Asupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings agree, however, with other studies in neurons, where HDAC6 inhibition alleviated abnormal A and tau accumulation [53,64], and with in vivo HDAC6-knockout in R6/2 mice showing no increase in mHtt aggregates [65]. Thus, as previously suggested [65], some of the effects of HDAC6 in cell-lines may not apply to neurons.…”
Section: Striatal and Cortical Neurons Differ In Mhtt Proteostasis Asupporting
confidence: 91%
“…Thus, as previously suggested [65], some of the effects of HDAC6 in cell-lines may not apply to neurons.…”
Section: Striatal and Cortical Neurons Differ In Mhtt Proteostasis Amentioning
confidence: 83%
“…HDAC6 overexpression leads to the complete deacetylation of microtubules, whereas inhibition of HDAC6 by specific inhibitors, RNAi-mediated protein depletion, or genetic knockout increases microtubule acetylation. 26,45,46 Our results revealed that HDAC6 inhibition by tubacin or specific RNAi was able to efficiently rescue the decrease in a-tubulin acetylation induced by silencing EWSR1 in mitotic cells, which suggests the involvement of EWSR1 in microtubule dynamics via HDAC6. However, the molecular mechanisms are not yet explored.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, another group showed that genetic depletion of HDAC6 did not modify the progression of Hungtinton's disease 49 . It was also shown that phosphorylation of HDAC6, activating its deacetylase activity, promotes proper aggresome formation and protects from toxicity 50 .…”
Section: Discussionmentioning
confidence: 99%